A Theoretical and Empirical Analysis of the Process of Nominal Convergence in Transition Countries with a Particular Emphasis on the Czech Economy - Žďárek, Václav, 1979-; Komárek, Luboš, 1971-; Dědek, Oldřich; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
This PhD thesis aims at exploring price convergence in the European Union with a particular emphasis paid to the Czech Republic and new EU member states. Fundamental issues are discussed in the first chapter, starting with the notion and term `convergence' since many alternative definitions have been proposed in the literature. Apart from that, main indicators utilized when investigating price convergence are defined (for example purchasing power parity/purchasing power standard, PPP/PPS, comparative price level, CPL) and a brief review of the literature is added. The second chapter deals with several issues accompanying price convergence in general and in transforming countries in particular such as the club convergence hypothesis, issues of tradability, availability of datasets and their strenghts and weaknesses, the link between price levels and rates of inflation, and determinants. Both `standard' and `modern' approaches are utilized in the last chapter so that several hypotheses can be verified. For the sake of comparability, individual CPLs for EU-27 countries for the period 1995(9)-2011 are employed. Firstly, stylised facts for both old EU and NMS are presented (including effects stemming from the on-going financial crisis). Secondly, the club convergence hypothesis is examined with help of two different ways - cluster analysis and the Phillips-Sul test (both for the EU and its `subgroups'). Both of them do confirm the existence of convergence clubs in the EU (including its old and new part). Following the previous findings, a somewhat broader and richer view on price level dynamics is supplemented via utilization of the so-called Stochastic kernel (Quah, 1993). This methodology shows both convergence and divergence (divergence/polarization/stratification) in the EU. Finally, the last section of this chapter is focused on a thorough search for determinants of price levels in the EU.
The Bayesian approach is employed (Bayesian model averaging, BMA) and our results confirm both the importance of both `traditional' determinants such as labour costs and output gap and new ones such as broadly defined institutional factors. Main findings of this thesis are summarized and commented in the conclusion aiming at providing implications for policymakers and some guidance for future research.
Vedoucí práce: Luboš Komárek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations